JACK'S AND ROSE'S STRUGGLE FOR LOVE IN JAMES CAMERON'STITANIC (1997) MOVIE : A MARXIST APPROACH - YULIANI, LULUT INDAH (2011)
The major problem of this study is to reveal the class struggle in Titanic (1997) movie. The objective of this study is to analyze the movie based on its structural elements and based on Marxist approach. In analyzing Titanic (1997), the writer uses qualitative method and Marxist approach. The object of the study is Jack's and Rose's Titanic movie published in 1995 , written, co-produced, and co-edited by James Cameron. The primary data source is the script, and the secondary data sources are the other data related to the analysis such as the author's biography and some reference books. The method of data collection is library research by collecting and recording both of the primary and secondary data. The technique of data analysis used in this study is descriptive analysis. The findings of the study show that. First, Titanic Movie illustrates the different stratification at Edwardian Period, the condition of aristocracy and lower or working class.. this different stratification creates a problem, that is the gap between them and the insulation to the lower rank by the higher one. The social relation have to hold on the equal rank of both sides, between men and women and this condition needs to criticize further.Second James Cameron in this movie "reconstructs" or re-presents the social condition of the Edwardian Period in order to reflect a similar issue of social relation and at the same time criticizes it. He tries to bridge the gap between the higher and the lower levels of social class by rebelling against the social stratification. The break of the stratification is symbolized in the love affair between the major characters.